Assignment of capacitance spectroscopy signals of CIGS solar cells to effects of non-ohmic contacts - Lauwaert, Johan; Van Puyvelde, Lisanne; Lauwaert, Jeroen; Thybaut, Joris W.; Khelifi, Samira; Burgelman, Marc; Pianezzi, Fabian; Tiwari, Ayodhya N.; Vrielinck, Henk (Solar energy materials and solar cells, 2013)
We report evidence for the identification of the capacitance transients detected at room temperature for thin-film photovoltaic cells with CIGS absorbers as an additional non-ohmic contact in the structure with a time constant larger than that of the solar cell p–n junction. The N1 signal was recently interpreted as a back contact barrier for which the RC-like time constant is smaller than the time constant of the junction. In this work we unite these experimental observations in one model. Since for a Mo/CIGS/CdS/ZnO solar cell several interfaces are connected in series, we introduce the idea of modeling capacitance spectroscopy signals based on RC-circuits in series for each interface. It is shown that the distinct features observed in capacitance spectroscopy of CIGS solar cells can be mimicked using this circuit as an electrical model. The differential equation for this structure as a function of time is solved numerically. It is inherent to the model that the transients in such a structure are voltage transients over each of the interfaces and that the transients are coupled. These findings question the practical use of capacitance spectroscopy for direct measurement of defects in the absorber layer. ► We show that the transients at room temperature in CIGS originate from an RC-contact. ► We model DLTS and AS signals based on RC-circuits. ► We question the use of DLTS or AS for direct observation of defects.